Aqueous Extracts of Mushrooms Enriched with Ergothionein with Antioxidant Activity and Its Effect on Human Dermal Fibroblasts UV irradiated - Anabell Del Rocío Urbina-Salazar; Alberto Renato Inca-Torres; Bryan Anthony Urbina-Salazar; Valeria Fernanda Inca-Torres; Juan Bautista (ESPOCH Congresses, 2021)
Abstract Ergotioneine (ERG) has potential applications as food additive and as an antioxidant for the treatment and/or prevention of diseases related to oxidative stress. In this work, we study the nature of antioxidant activity and investigate the effect of aqueous extracts of Agaricus bisporus enriched with ergotioneine (EAHE-ERG), a natural product, obtained through enzymatic digestion and membrane technology, in cellular response induced by UV, in crops fibroblasts. EAHE-ERG suppressed by the increase of TNF-α by UV-B radiation. Furthermore, in fibroblasts exposed to UV-A, EAHE-ERG suppressed the expression of matrix metalloproteinase-1 protein (MMP-1) in almost 50% and reduced the RNAm expression from MMP-1. From these results, we conclude that EAHE-ERG can reduce anti-aging effects of the skin from UV radiation by removing O 2 and 1O 2 , and the reduction protease signs and inflammatory activity.